A prospective randomized study of the difference in diagnostic yield between endoscopic ultrasound-guided fine-needle aspiration (EUSFNA) needles with and without a side port in pancreatic masses - Ang, Tiing Leong; Kwek, Andrew Boon Eu; Seo, Dong Wan; Paik, Woo Hyun; Cheng, Tsu-Yao; Wang, Hsiu-Po; Lau, James (Endoscopy International Open, 2015)
Background and study aims: Two 22G needles with similar designs, apart from the absence (A) or presence of a side port (B), are available for endoscopic ultrasound (EUS)-guided fine-needle aspiration (FNA). The side port was designed to increase diagnostic yield but this advantage was unproven. This study evaluated the difference in diagnostic yield between both needles in pancreatic masses.Patients and methods: This was a prospective multicenter randomized cross-over study. Patients with pancreatic masses were randomized to one needle for the first two passes, followed by the other for the next two passes. A pathologist blinded to the needle assessed each puncture for cellularity and morphology. The diagnostic yield between both needles was compared.Results: In total, 30 patients were recruited (mean lesion size: 3.5 cm, range: 1.2 – 6.3). Comparison of cellularity adequacy: first pass: A vs. B: 26/30 vs. 24/30 (P = 0.488): 2nd pass: A vs. B: 25/30 vs. 26/30 (P = 0.718). Comparison of diagnostic accuracy: first pass: A vs. B: 22/30 vs. 23/30 (P = 0.766); after two passes: A vs. B: 26/30 vs. 26/30 (P = 1.0). When all four passes were assessed, adequate cellularity was obtained in 29/30 and the correct diagnosis was obtained in 28/30 patients. There were no procedural complications.Conclusions: There was no significant difference in diagnostic yield between EUSFNA needles with or without a side port for pancreatic masses.Study registration: NCT02092519.